Current Capacities of Digital Forensics for Investigations of Different Types of Crimes - D. V. Zav’yalova (Теория и практика судебной экспертизы, 2020)
The article focuses on the present state of digital forensics and its potential when investigating different types of crimes with a “digital” element. It also presents a brief historical overview of the development of digital forensics as an independent type of forensic examination, its theoretical framework.The paper presents a summary of the practice of the Laboratory of Digital Forensics of the Russian Federal Centre of Forensic Science of the Russian Ministry of Justice over 2017–2019. In the course of the summary, the author analyses typical questions to experts, the percentage of cases’ categories, the most common objects of the expertise, and experts’ opinions, their form, and completeness. Following the summary’s results, the most frequent investigators’ requests for this kind of examination have been highlighted. Also, typical errors at appointing the expertise have been revealed.The author presents a prognosis for the further development of digital forensics and proposes strategies and measures to minimize the errors at the appointment of the examinations and unsustainable expenditure of resources in appointment and conduct of this type of research.